God's strange messengers: Carl McIntire and the fundamentalist exploration of the flying saucer question - Schmidt, Daved Anthony (Nova religio, 2016)
This essay examines the relationship between the thought and ministry of Carl McIntire and the subject of flying saucers. McIntire was a prominent American fundamentalist in the middle decades of the twentieth century. His interest in UFOs culminated in 1973 with the formation of the 20th Century UFO Bureau. McIntire and his associate Robert “Bob” Barry provide an opportunity to build upon recent scholarship that explores the ways Christians positively engaged the subject of flying saucers. I argue that his conservatism led to his interest the subject and that he drew from both theological and Theosophical influences to form his interpretation. I argue further that, understood within the context of his broader ministry, his interest arose from what he perceived to be the religious challenges brought about by space exploration. McIntire’s interests ultimately demonstrate the malleability of Christian “orthodoxy,” even among its most staunch defenders.